Quality Management Practices of Select Real Estate Companies: An Experienced-based Approach - Rallang, Florendo M.; Gutierrez, Ernell Bautista (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
roviding quality services is a must for all type of industry and the requirement is not different from the industry of real estate. As mentioned by Chege, S & Bett S (2019), the real estate industry is one of the most important industries for the development and economy of a nation and therefore important that adequate measures are put in place to ensure quality in the sector. This study investigated the quality management systems of select real estate firms focusing on the following areas: Customer Focus, Leadership, Involvement of People, Process Approach, Continual Improvement, Factual Approach to Decision Making and Mutually Beneficial Supplier Relationship. Indicated in the study of Quiambao, J & Alvaro, K (2023), that the QMS practices dimensions top management leadership, customer orientation, process control and improvement, and employee engagement each had significant positive impact on each business performance perspectives financial, customer, internal business processes, and innovation and learning of the subject government corporation Likewise, the study identified following themes focusing on areas of real estate quality management practices were culled out” Client Determination, Keeping Clients Satisfied, Handling Complaints, Direction Setting, Planning, Alignment and Empowerment, Communication, Opportunities and Growth, Competence, Communication Enhancement, General Rule, Client Need, Efficiency and Effectiveness, Firm Reputation, Accessibility of Data, Word of Honor, Act of Appreciation and Fairness and Quality.